Relationships between organizational commitment, job satisfaction and stress with intention to leave among employees of Appfuxion Consulting Sdn Bhd - Mohamad Syafiq, Mohamad Saad (2018)
This research aims to examine the relationships between organizational commitment, job stress and job satisfaction with the intention to leave among the employees of AppFuxion Consulting Sdn Bhd. The study was conducted using the descriptive research method to ensure that the data collected meet the research objectives. Some 92 samples were collected from the employees of AppFuxion Consulting Sdn Bhd with about a total of about 120 population. The quantitative analysis, Cronbach Alpha test and Pearson Correlation test were performed using the Statistical Package for Social Science (SPSS) Version 23.0. This research also involved a cross-sectional review of the previous researches on the factors that influenced the intention to leave among employees in other sectors. Job stress are significant positive relationship between intention to leave and job stress with (β = 0.837) and (p = 0.000). Job satisfaction are significant negative relationship between intention to leave and job satisfaction with (β = - 0.008) and (p = 0.942). Organizational Commitment are significant positive relationship between intention to leave and organizational commitment with (β = 0.012) and (p = 0.925). It shown that all three independent variable have influence toward intention to leave.